AN OCCULT DISEASE… AND ONE THAT CHANGED MY PRACTISE. Issue 10 (9th September 2014) - Shatti, David; Price, Chris; Luppe, Sebastian; Scolding, Neil
Abstract : Neuromyelitis optica (NMO) and NMO spectrum disorder are well characterized demyelinating neurological conditions with established but evolving diagnostic criteria. Antibody mediated inflammation underpins their aetiology, in particular relating to antibodies to the aquaporin-4 transmembrane channel. NMO forms an important differential diagnosis to multiple sclerosis, requires a different treatment strategy and is therefore important to discriminate. A middle-aged woman presented with an acute inflammatory encephalopathy with subsequent brainstem relapse. Aquaporin-4 antibodies were positive. Following routine examination, a breast lump, subsequently diagnosed as locally invasive adenocarcinoma of the breast, was diagnosed. This was surgically resected. Initially treatment with methylprednisolone, and a subsequent course of plasma exchange with adjuvant chemotherapy led to an exponential recovery; 18 months later repeat antibody titres were negative and the patient had a residual mild spastic quadraparesis and ataxia. This case complements an evolving data set of paraneoplastic NMO and highlights the need to consider underlying neoplasia when making this diagnosis. Specific treatment of such underlying pathology, alongside appropriate immunosuppressive treatments, remain key therapies in this context and can secure a sustained neurological recovery.